2012
DOI: 10.1186/1748-717x-7-207
|View full text |Cite
|
Sign up to set email alerts
|

Radiation treatment with volumetric modulated arc therapy of hepatocellular carcinoma patients. Early clinical outcome and toxicity profile from a retrospective analysis of 138 patients

Abstract: BackgroundTo report early outcome and toxicity for inoperable patients with hepatocellular carcinoma (HCC) treated with volumetric modulated arc therapy (VMAT).MethodsOne hundred and thirty eight patients were retrospectively analysed. Dose prescription ranged from 45 to 66Gy with conventional fractionation regime. Based on AJCC staging, 88.4% presented stage III or IV. Two-thirds (69.6%) were Child-Pugh stage A, the remaining were stage B. According to Barcelona Clinic Liver Cancer staging, 72.5% of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 22 publications
0
16
1
Order By: Relevance
“…Both severe gastrointestinal AE and radiation-induced liver disease (RILD) have been reported after treatment of HCC with volumetric modulated arc therapy [35]. In contrast, neither severe (grade ≥ 3) RILD nor gastrointestinal AE was observed in the present study.…”
Section: Discussioncontrasting
confidence: 78%
“…Both severe gastrointestinal AE and radiation-induced liver disease (RILD) have been reported after treatment of HCC with volumetric modulated arc therapy [35]. In contrast, neither severe (grade ≥ 3) RILD nor gastrointestinal AE was observed in the present study.…”
Section: Discussioncontrasting
confidence: 78%
“…Yoon et al 48 reported RILD in 2/65 patients (3.1%) treated with HT and concurrent transarterial chemoinfusion; median survival time (20 months) was similar to the present study. Wang et al 50 described a response rate of 64% in 138 HCC patients treated with VMAT, 34 (25%) of which developed RILD. As HCC is always surrounded by normal liver parenchyma, rotational IMRT modalities may not offer more liver protection than IMRT.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, it has been shown that 5-10% of patients who receive 30-35 Gy of radiation to the whole liver experience RIHT [ 12 ]. However, several recent studies showed that partial irradiation of the liver with higher doses is possible with the advancement of radiation techniques [ 7 11 ]. An effective radiation dose can be delivered within an acceptable range of RIHT.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, the role of radiotherapy in HCC patients was limited because of the poor tolerance of the whole liver to radiation [ 4 ]. However, with advances in radiotherapy techniques, such as three-dimensional conformal radiotherapy (3D-CRT), intensity-modulated radiotherapy (IMRT), and helical tomotherapy, several studies have been published reporting the clinical outcomes of these therapies [ 2 , 5 11 ]. In addition, several clinical and dosimetric parameters have been suggested for predicting the development of radiation-induced hepatic toxicity (RIHT), because the toxicity to the liver is the greatest impediment to improving clinical outcomes [ 4 , 12 19 ].…”
Section: Introductionmentioning
confidence: 99%